Kepatuhan Pola Diet dengan Kualitas Hidup Pasien Gagal Ginjal Kronik - Wahyuni, Endang; Lestari, Ratna (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Background of Study: End Stage Renal Disease was ranked in the sixth position as the death causal in all hospital in Indonesia, in 2006 with mortality rate 2521 people. The data according to Depkes DIY in 2007 state that there are 87 new cases of End Stage Renal Disease. In the end stage renal disease, proper nutrition and adequate food will give better quality of life. Preliminary study in the Hemodialysis unit RSUD Panembahan Senopati shows that, 20 patientswho runhemodialysistherapywith the diagnosisof end stage renal disease, fiveof them experiencededema, twopatients experiencedanorexia, with these data the researcher conclude that there are manypatients whodo notobey with their dietpattern. So it will make their quality life going decrease, it can be proved by weight lossand weight gainin edema patients. Objective:This Study aimed to know a corellation between the pursuance of diet pattern of end stage renaldisease with patient life quality in Hemodialisa Unit of RSUD Panembahan Senopati Bantul . Methods:This study used analysis descriptive with Cross Sectional design approach. The sample was taken with Consecutive Sampling. It means that 104 patients of end stage renal disease who are undergoing hemodialysis treatment in RSUD Panembahan Senopati Bantul were involved. Result:Most of the patientswho areundergoinghemodialysistherapyobeyin implementing the diet program of end stage renal disease. Most ofpatients who are sufferingend stage renal disease in hemodialysis unit of Panembahan Senopati Bantul local general hospitalhave agood quality of life. The pursuance of diet pattern with the quality of life in the patient of end stage renal disease has a Significatn Corellation. It was shown by the result of Kendal Taup-value 0,000 < 0,05. Conclusion:There is corellation between the pursuance of diet pattern of end stage renal disease with the quality of life of patients in hemodialysis unit of RSUD Panembahan Senopati Bantul Keyword : The pursuance of diet pattern, Quality of life.